Structure, Dynamics, and Allosteric Potential of Ionotropic Glutamate Receptor N-Terminal Domains - Krieger, James (Biophys J, 2015)
Ionotropic glutamate receptors (iGluRs) are tetrameric cation channels that mediate synaptic transmission and plasticity. They have a unique modular architecture with four domains: the intracellular C-terminal domain (CTD) that is involved in synaptic targeting, the transmembrane domain (TMD) that forms the ion channel, the membrane-proximal ligand-binding domain (LBD) that binds agonists such as L-glutamate, and the distal N-terminal domain (NTD), whose function is the least clear. The extracellular portion, comprised of the LBD and NTD, is loosely arranged, mediating complex allosteric regulation and providing a rich target for drug development. Here, we briefly review recent work on iGluR NTD structure and dynamics, and further explore the allosteric potential for the NTD in AMPA-type iGluRs using coarse-grained simulations. We also investigate mechanisms underlying the established NTD allostery in NMDA-type iGluRs, as well as the fold-related metabotropic glutamate and GABA(B) receptors. We show that the clamshell motions intrinsically favored by the NTD bilobate fold are coupled to dimeric and higher-order rearrangements that impact the iGluR LBD and ultimately the TMD. Finally, we explore the dynamics of intact iGluRs and describe how it might affect receptor operation in a synaptic environment.